Perservasi Pegetahuan Adat Bagi Keberlangsungan Indigenous Knowledge Masyarakat Kapur XI Kabupaten Lima Puluh Kota Kanagarian Duriantinggi - Rahmad, Fajri; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractÂ This study aims to examine and assess how theÂ  kanagarian duriantinggi community maintains and continues the indigenous knowledge found there. Indigenous Knowledge of the Durian Tinggi people, The research method used is descriptive case study, Data collection methods in this study were observations, interviews, and documentatio. The results of this study show that the people in Kanagrian Duriantinggi have different knowledge of adat from other communities where the culture found in Kanagarian Duriantinggi has a little element of Malay culture in it, the culture that is still on the run and continues to be passed on from generation to generation in the people of Kabagrian Duriantinggi. Whereas in the conservation of knowledge contained in the community more in the form of documentation, whereas for text or text is only rewritten and does not use document rext digitall, indigenous knowledge (indigenous knowledge held by the community in Durian Tinggi, indigenous knowledge is stored within each community verbally.Keywords: preservation of knowledge, indigenous knowledge, Durian tinggi community